Strategi dan Etika di Era Digital pada Pemanfaatan Kecerdasan Buatan dalam Hubungan Masyarakat - Angin, Tabitha Gloria Perangin; Mukhlisiana, Lusy (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Rapid technological advances in the 21st century have brought significant changes to various industries, including public relations (PR). One of the key innovations driving this transformation is artificial intelligence (AI). This study aims to comprehensively examine the role of artificial intelligence (AI) in public relations (PR) by highlighting how this technology influences communication strategies, operational efficiency, and the dynamics of interaction between organizations and stakeholders. Using a Systematic Literature Review (SLR) approach, the findings indicate that AI enhances the efficiency of communication strategies through task automation, sentiment analysis, and improved message personalization. However, the implementation of AI presents various challenges, particularly in ethical and legal aspects. Issues such as data privacy, algorithmic bias, and transparency are key concerns that require strict oversight. It is crucial for PR professionals to understand and comply with existing legal frameworks to avoid legal risks, protect organizational reputation, and ensure the sustainability of relationships with stakeholders.